PERAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA SMP MUHAMMADIYAH 2 CIREBON: The role of the family environment on the learning achievement of students at Muhammadiyah 2 Middle School, Cirebon - Sofandi; Anisa Musyarrof (UI Cirebon (Universitas Islam Cirebon), 2025)
Some students at Muhammadiyah 2 Cirebon Middle School have not yet achieved optimal learning outcomes, partly due to limited parental involvement and low awareness of the importance of supporting their children’s education. This study aims to analyze the role of the family environment in influencing student learning achievement. The research employed a qualitative approach with data collected through in-depth interviews. The findings indicate that parental involvement plays a crucial role in improving student performance. Efforts made by parents include providing motivation, creating a comfortable learning atmosphere at home, limiting children’s recreational screen time, and facilitating additional tutoring outside school. The study concludes that a supportive family environment, characterized by effective communication and positive parental behavior, is essential for fostering students’ enthusiasm for learning and enhancing their academic achievement. Conversely, a lack of parental attention may lead to a less conducive learning environment, reduced motivation, and lower academic performance.